Analysis of the Influence of Digital Capabilities, Dynamic Capabilities, and Strategic Entrepreneurial Behavior on Business Model Innovation and Business Performance: An Empirical Study of SMEs in Indonesia - Addini Zainuba; Siti Nursyamsiah (Indonesian Journal of Business Analytics, 2025)
Examining the relationship between internal organizational characteristics and innovation and performance results in small and medium-sized businesses (SMEs) is the goal of this study. Through the use of structured questionnaires and a quantitative research methodology, information was gathered from 166 SMEs in Indonesia's various industries. Structural Equation Modeling using Partial Least Squares (SEM-PLS) was used to analyze the data. The findings show that business model innovation, which in turn has a major impact on business performance, is significantly positively impacted by digital skills, dynamic capabilities, and strategic entrepreneurial behavior. Additionally, the impact of these three organizational characteristics on business performance is mediated by business model innovation. In addition to making theoretical contributions to the literature on strategic management and business model innovation, the findings give SME stakeholders useful insights into how to prioritize digital transformation and innovation strategy.